Metal-Organic Framework-Based Nanotherapeutics With Tumor Hypoxia-Relieving Ability for Synergistic Sonodynamic/Chemo-therapy - Zhong, Lichang; Yang, Tian; Li, Pei; Shi, Lin; Lai, JinYu; Gu, Liping (Frontiers in Materials, 2022)
The methods of clinical treatment for tumor include surgical treatment, radiotherapy, and chemotherapy, which have been found to have many side effects and cannot meet the urgent need in clinic. As one of the typical characters in tumor microenvironment, hypoxia impedes therapies to cancer patients. Therefore, we fabricated an advanced biological responsive therapeutic system, DOX/Ce6@ZIF-8@PDA(DZCP), to simultaneously doxorubicin （DOX）and O2-enhanced combination treatment. Notably, DOX and tumor hypoxia destruction, improving the sonodynamic therapy (SDT) efficiency of chlorin e6 (Ce6). Moreover, polydopamine (PDA) promotes the endocytosis of cells and enhances the ability of drugs to enter cancer cells. The in vitro and in vivo results demonstrate that DZCP is able to cause impressive tumor inhibition through enhanced combination of DOX and Ce6 under SDT, indicating aa new possible method for cancer therapy.